The battle for the fourteenth colony America's war of liberation in Canada, 1774 - 1776 - Anderson, Mark R. (Univ. Press of New England, 2013)
"In this dramatic retelling of one of history's great "what-ifs", Mark R. Anderson examines the American colonies' campaign to bing Quebec into the Continental confederation and free the Canadians from British "tyranny." -- jacket flap
Includes bibliographical references (pages 417-429) and index
Keywords: Geschichte 1774-1776; Canadian Invasion, 1775-1776; Geschichte; Nordamerikanischer Unabhängigkeitskrieg; Invasion; Québec (Québec) / History / Siege, 1775-1776; United States / History / Revolution, 1775-1783 / Campaigns; USA; Québec